Control Reconfiguration of Dynamical Systems Linear Approaches and Structural Tests - Steffen, Thomas (Lecture Notes in Control and Information Sciences, 2005)
Fault-tolerant control concerns the operation of the system after a fault has occurred. Unlike the classical control theory, where the behaviour of the system is completely defined, fault-tolerant control has to deal with situations where the system has been damaged. Therefore, the system may not react the way it was designed to. Reconfiguration is an approach for fault-tolerant control. The idea is to change the control structure in response to the fault. If a sensor signal is lost, the relevant state of the plant has to be observed instead of being measured directly. The book extends this idea to actuator faults: if an actuator gets stuck, another actuator can be used to control the same state, and to close the control loop again. This approach is called {}``virtual actuator'', and it is studied in detail in the first half of the book. The second half introduces structural analysis as a tool for reconfiguration. Because a fault changes the structure of the system, the reconfiguration solution is sought on a structural level. The system model is abstracted from the specific parameters, and represented by a directed graph. Novel algorithms are presented to test for reconfigurability and to find a reconfiguration solution. A MATLAB toolbox is supplied, which contains the main algorithms and examples. The book addresses advanced engineering students, developers and researchers that have a specific interest in control reconfiguration. A good understanding of multi-variable dynamic systems is helpful, but the second part is accessible even without this.